The hierarchy of value-based components within the “happiness” concept in the Russian linguistic consciousness - Nikonova, Zhanna Viktorovna (SHS web of conferences, 2021)
The article considers the value-based component of the “happiness” concept in the Russian language as one of the main concepts in the Russian national consciousness. The study aims at determining and describing the hierarchy of such components in the Russian language. It supplements the current linguistic information about the content of the above-mentioned concept by revealing the hierarchy of its value-based components in the Russian linguistic consciousness. This approach is used to study the “happiness” concept in the Russian language for the first time and proves the scientific novelty of this research. The theoretical basis is formed by postulates of modern cognitive linguistics about concepts as units of a personal conceptual system in their relation to linguistic expressions containing information about the world, as well as concepts as national images (ideas or symbols) complicated by individual representation. The research subject is the hierarchical connections among value-based components of the “happiness” concept in the Russian linguistic consciousness objectified by various verbal means and acting as determinants of the concept’s name. The main objective is to identify the hierarchy of value-based components of the above-mentioned concept and reveal its specifics in the Russian linguistic consciousness. The research material consists of the linguistic facts obtained in the course of a free-association experiment conducted at the end of January 2021 by questioning users of the social network VKontakte. The questionnaire explained the goals and objectives of the experiment and provided an incentive for an associative array of 10 positions to the concept under study. After analyzing the results of this psycholinguistic experiment, the authors have established that the “happiness” concept in the Russian language has a clear hierarchy of value-based components, which highlights the specific conceptualization of such an abstract category as “happiness” in the linguistic consciousness of native Russian speakers.